Emergencies in Urology - Hohenfellner, M.; Santucci, R.A (Springer Berlin Heidelberg : Imprint: Springer, 2007)
Emergencies in Urology is a comprehensive textbook covering one of the few remaining white spots on the map of urological literature. To date only a small number of publications have been dedicated to the topic of urgent and emergent problems in urology - important as these are in our daily clinical life.Therefore the editors, both of them internationally recognized urological experts, have taken the effort to present an in-depth study into virtually every possible urgent urological situation with which a urologist may be confronted today. Consequently, the book includes chapters on topics such as urological trauma, urosepsis, urinary obstruction, oncological emergencies, intra- and postoperative complications, acute problems in children, and many more.To obtain the best possible expertise in such a wide field, renowned expert authors have contributed their experience to this book. They did so not only by writing the regular book chapters but also by delivering short stories about urgent situations they encountered in their own professional life. These vignettes are one of the rare opportunities where experience can be relayed without restriction from one urological generation to the next.Much work has gone into the illustrations for the book. Foremost in this respect is the art of Stephan Spitzer, one of the leading medical illustrators of today.The result is a comprehensive, well-organized text, in which state-of-the-art know-how, didactic algorithms, personal experience and detailed illustrations are combined into a unique guide of how to manage urological emergencies.